Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

f(m)=m^5+3m^4-21m^3-12m^3-12m^2=31m-33 at m=6

Sagot :

Answer:

False

or

3951

Step-by-step explanation:

F(m) represents an equation that when the "m" is changed within the parenthesis, all the m's in the equation change as well. The function determines the value of the equation.

In this case, "m = 6" or in basic terms:

f(6) = m^5 + 3m^4 - 21m^3 - 12m^3 - 12m^2 = 31m - 33

Replace all m's with 6.

[tex]f(6) = (6)^5 + 3(6)^4 - 21(6)^3 - 12(6)^3 - 12(6)^2 = 31(6) - 33[/tex]

And do the exponents + coefficients.

6^5 = 7776

3(6^4) = 3888

-21(6)^3 = -4536

-12(6)^3 = -2592

-12(6)^2 = -432

31(6) = 186

-33 = -33

Our final equation is:

7776 + 3888 - 4536 - 2592 - 432 = 186 - 33

Add/subtract all together:

4104 = 153

Now because of your question being quite vague, there could be two ways of answering.

One: Determining whether the equation is true or false, which in this case. 4104 does indeed not equal 153, therefore making it false.

Two: Getting one single number, which we would have to subtract 153 from both sides to get the answer:

4104 - 153 = 153 - 153

[3951]